Research on spatial environmental quality and driving forces in Chaohu region based on PSR modelling - Zhang, Le; Yuan, Mingxia; Guo, Yanlong (Frontiers in Earth Science, 2025)
Against the backdrop of accelerating environmental pollution driven by rapid urbanisation, understanding the spatial evolution patterns of environmental quality in typical lake basins is crucial for regional sustainable development. This study focuses on the Chaohu region of China (comprising 1 city, 1 district, and 3 counties). Based on the Pressure-State-Response (PSR) model, a multi-dimensional indicator system incorporating both natural and human factors was established. Combining the Entropy Weight-TOPSIS method with ArcGIS, we assessed the spatial environmental quality from 2019 to 2023. The results indicate: 1) During the study period, the spatial environmental quality of the basin showed a fluctuating upward trend, with the relative proximity of spatial environmental quality in the Chaohu region increasing to 0.536, exhibiting significant phased fluctuations. 2) Environmental quality exhibits a spatially differentiated pattern with higher quality in the northwestern region and lower quality in the southeastern region. Among these, Baohe District has the best environmental quality, Feixi County and Feidong County have relatively good environmental quality, while Chaohu City and Lujiang County have relatively poor environmental quality; 3) Comparing the weight coefficients of various indicators, among the 19 indicators in the PSR framework, the five indicators with the highest weight coefficients were annual average sulphur dioxide concentration (P3), per capita disposable income of urban households (S2), added value of the tertiary industry (R2), fiscal expenditure on energy conservation and environmental protection (R4), and gross domestic product (R6). The Chaohu River Basin requires differentiated governance strategies to balance urbanisation and ecological protection—urban areas with dense populations should strengthen pollution control and invest in green infrastructure, while ecologically sensitive areas must strictly adhere to resource consumption red lines. The ‘zonal governance’ strategy proposed in this study provides a reference framework for the governance of similar lake basins.